Analysis of the Impact of the COVID-19 Pandemic on Lobster Cultivation Activities (Panulirus spp.) in East Lombok Regency - Mohammad Subhan; Junaidi Junaidi (Department of Aquaculture, 2022)
The COVID-19 pandemic has caused lobster cultivators (Panulirus spp.) in East Lombok Regency to try to fulfill their daily needs by looking for other jobs. The purpose of this study was to determine the impact of the COVID-19 pandemic on the sustainability of the lobster cultivation business in East Lombok Regency. The research method used was descriptive qualitative method based on the data generated during the research. Analysis of the data used in this research was the Net Benefit Cost Ratio to determine the amount of net profit from costs and investments. Stakeholder perceptions were analyzed descriptively. The results of the analysis show that the lobster cultivation business is still feasible to do, so it can be concluded that the COVID-19 pandemic has no impact on the sustainability of the lobster cultivation business in East Lombok Regency. To maintain the continuity of lobster cultivation in East Lombok Regency, it is necessary to ensure the availability of feed and guarantee access to marketing.